Social Work in Africa Exploring Culturally Relevant Education and Practice in Ghana - Kreitzer, Linda (Africa: Missing Voices, 2012)
Social Work in Africa offers professors, students, and practitioners insight concerning social work in the African context. Its purpose is to encourage examination of the social work curriculum and to demonstrate practical ways to make it more culturally relevant. Drawing on her experience as a social work instructor in Ghana with field research conducted for her doctoral thesis, author Linda Kreitzer addresses the history of social work in African countries, the hegemony of western knowledge in the field, and the need for culturally and regionally informed teaching resources and programs. Guided by a strong sense of her limitations and responsibilities as a privileged outsider and a belief that "only Ghanaians can critically look at and decide on a culturally relevant curriculum for themselves," Kreitzer utilizes Participatory Action Research methodology to successfully move the topic of culturally relevant practices from rhetoric to demonstration. Social Work in Africa is aimed at programs and practise in Ghana; at the same time, it is intended as a framework for the creation of culturally relevant social work curricula in other African countries and other contexts.